Are Psychometric Tools a Viable Screening Method for Small and Medium-Size Enterprise Lending? Evidence from Peru - Arraiz, Irani; Bruhn, Miriam; Ruiz Ortega, Claudia; Stucchi, Rodolfo (World Bank, Washington, DC, 2017)
This study collaborated with the Entrepreneurial Finance Lab and a large bank in Peru to use psychometrics for small and medium-size enterprise lending. Applicants used a psychometric tool and those who achieved a score higher than a threshold were offered a loan. Using a regression discontinuity design and credit bureau data, the study finds that the tool increased small and medium-size enterprise loan use by up to 59 percentage points for applicants without a credit history, without leading to worse repayment behavior. This increase in borrowing resulted primarily from financial institutions other than the partner bank. For applicants with a credit history, the tool did not increase small and medium-size enterprise loan use.